Online explainer videos: Features, benefits, and effects - Schorn, Anna (Frontiers in Communication, 2022)
Explainer videos are short films that explain abstract concepts and relationships, usually in an educational context. They apply storytelling techniques and focus on relevant facts using different visualizations. However, when reviewing the literature, it becomes evident that there is no universally applied definition for explainer videos and no consistent categorization. The vast majority of studies investigate explainer videos as learning tools, although many explainer videos follow persuasive goals. There are very little studies on the persuasiveness, which is problematic because explainer videos appear to be more than an important learning or teaching tool; rather, they are an activistic tool for promoting scientific topics and are a crucial marketing measure. In particular, in the context of science communication, it appears essential to investigate the impact on attitude and behavioral outcomes because there are numerous high-reach videos on YouTube that contradict scientific consensus. At the same time, explainer videos apply storytelling techniques, an informal communication style, and combine an off-voiceover with clear animations, which might lead to eased processing fluency and a positive experience, fostering persuasive outcomes. This mini review elaborates on these research gaps and compiles the state of research on explainer videos, with a focus on persuasive effects in informal settings, drawing on concepts from (science) communication and education.